BRONCHOPULMONARY LESIONS AND QUALITY OF LIFE IN PATIENTS WITH RHEUMATOID ARTHRITIS - M. V. Sheyanov; I. S. Schedrina; V. A. Sulimov (Klinicist)
Aim – assessment of quality of life (QoL) in patients with rheumatoid arthritis (RA) with the presence and severity of bronchopulmonary lesions.Materials and methods. The study included 104 patients with RA and 100 patients not suffering from RA and verified chronic respiratory diseases. The analysis of the QOL of patients using questionnaires EQ-5D (EuroQoL Group, 1990) and SGRQ (St. George's Hospital questionnaire to assess respiratory function), performed spirometry, bodyplethysmography , pulse oximetry, the definition of lung diffusioncapacity, multispiral computed tomography of the lungs.Results. Performance of all scales and the resulting indices of questionnaires EQ-5D and SGRQ showed a significant decrease in QoL ofRA patients compared with those in control group and the general population. A correlation index of EQ-5D with vital capacity (r = 0.47;p < 0.001) and diffusion capacity (r = 0.67; p < 0.01) of the lungs is revealed. The main reason for the reduction of indices of the questionnaire SGRQ in patients with RA was the presence of shortness of breath. The multi-factorial origin of dyspnea in patients with RA with theessential role of bronchopulmonary lesions was established.Conclusion. Bronchopulmonary lesions in the underlying disease have an adverse impact on the QOL of patients with RA. Promising directions for improving the QOL of RA patients with bronchial lesions can be considered for activities for the conservation of respiratory lung function, exercise control RA activity, elimination of anemia correction of psycho-emotional disturbances of anxiety-depressive character.